2018
DOI: 10.1016/j.neurobiolaging.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa improves response inhibition and enhances striatal activation in early-stage Parkinson's disease

Abstract: Dopaminergic medications improve the motor symptoms of Parkinson's disease (PD), but their effect on response inhibition, a critical executive function, remains unclear. Previous studies primarily enrolled patients in more advanced stages of PD, when dopaminergic medication loses efficacy, and patients were typically on multiple medications. Here, we recruited 21 patients in early-stage PD on levodopa monotherapy and 37 age-matched controls to perform the stop-signal task during functional magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 103 publications
5
21
0
Order By: Relevance
“…As reported previously, both in the LPD and RPD groups, 7 patients of 17 were under dopaminergic treatment. As it has been suggested that dopaminergic treatment improves inhibitory control in early‐stage PD patients, but not in moderate to advanced patients, we assessed whether those patients of our sample who were under drug therapy had a better reactive inhibition with respect to drug‐naïve patients. As reported in Supplemental Data 6, we did not find any difference between treated and untreated patients.…”
Section: Resultsmentioning
confidence: 99%
“…As reported previously, both in the LPD and RPD groups, 7 patients of 17 were under dopaminergic treatment. As it has been suggested that dopaminergic treatment improves inhibitory control in early‐stage PD patients, but not in moderate to advanced patients, we assessed whether those patients of our sample who were under drug therapy had a better reactive inhibition with respect to drug‐naïve patients. As reported in Supplemental Data 6, we did not find any difference between treated and untreated patients.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, many treatments of PD target the putamen and/or SNc, including L-DOPA as the first-line medication. L-DOPA restores dopaminergic signaling and improves motor control including response inhibition by enhancing striatal activation in early-stage Parkinson's disease (Manza et al, 2018). High-frequency deep brain stimulation of the putamen (Montgomery et al, 2011), low-frequency deep brain stimulation of the SN pars reticulata (Valldeoriola, 2019;Weiss et al, 2019), and crocin (Haeri et al, 2019) for treatment-refractory patients have also demonstrated efficacy in the treatment of PD.…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact effects of l ‐dopa on decision‐making are still unclear. Indeed, experimental data suggest that l ‐dopa can impair (e.g., by increasing impulsive activation of muscles), improve (e.g., by increasing response inhibition), or not influence cognitive processes involved in decision‐making as well as inhibitory processes. According to computational models of decision‐making, a hyperdopaminergic state could lead to failure of the cognitive processes involved in decision‐making .…”
mentioning
confidence: 99%